Bicentennial heroines: Female representation in the numismatic series “Women in the Independence process of Peru” - Reyes Fernández, Alexandra (2022)
The present research arises from the production and circulation of the numismatic series “La mujer en el proceso de Independencia del Perú” as part of the activities developed for the Bicentennial of the Independence of Peru. The main objective is to investigate the narrative of the nation from the female figures of heroines represented in this series. On the one hand, concepts such as the nation and banal nationalism are presented to lay the theoretical framework. Then, the main feminine iconographic representations in the country’s coins will be explained. Likewise, based on official information, the objectives of the production and circulation of the series in question are exposed. On the other hand, based on a set of interviews, the meaning of this series is explained from the point of view of a group of coin collectors, as well as members of the Central Reserve Bank of Peru. From this, their impressions of the series will be taken into account, as well as its meanings. Finally, this article will end with some final thoughts on the main findings of this research.